2018
DOI: 10.1590/0103-6513.20170093
|View full text |Cite
|
Sign up to set email alerts
|

QFD and TRIZ integration in product development: a Model for Systematic Optimization of Engineering Requirements

Abstract: Paper aims: Proposal of a Model for Systematic Optimization of Engineering Requirements applied to product concept development and based on a two-level integration of the methods Quality Function Deployment (QFD) and Theory of Inventive Problem Solving (TRIZ). Originality: Requirements extraction directly from patent documents in order to identity the most relevant user requirements as well as the technical requirements interactions through a QFD matrix. Then, TRIZ Contradiction Matrix is used to withdraw the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Developing new technologies or new approaches to existing means involves creating something that did not exist before to improve the current status quo. In the concept development phase, initial alternatives are usually generated and the technological systems with greater poten-tial for success for later development are selected (Naveiro & Oliveira, 2018). This is the case of the study published by Adamec et al (2016), in which a basic methodology approach to identify and analyse risks regarding cities' functional systems is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Developing new technologies or new approaches to existing means involves creating something that did not exist before to improve the current status quo. In the concept development phase, initial alternatives are usually generated and the technological systems with greater poten-tial for success for later development are selected (Naveiro & Oliveira, 2018). This is the case of the study published by Adamec et al (2016), in which a basic methodology approach to identify and analyse risks regarding cities' functional systems is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, this combined approach has demonstrated remarkable effectiveness in addressing identified challenges. For instance, a notable study conducted by Naveiro and de Oliveira [15] presented a model aimed at enhancing the engineering requirement system through the integration of the Quality Function Deployment (QFD) and TRIZ methods. This investigation involved the direct extraction of requirements from patent documents, intending to identify prevalent user interconnections via the QFD matrix.…”
Section: Related Researchesmentioning
confidence: 99%
“…According to Naveiro & Oliveira (2018), "QFD is used to transform subjective user demands into objective parameters, leading to the identification of engineering characteristics which may be relevant, and assigning priorities for system requirements." This study utilizes QFD tools to collect, organize and evaluate data, enabling the refinement and convergence of the demand towards the real customer expectations.…”
Section: Quality Function Deployment (Qfd)mentioning
confidence: 99%